Economies of scale and optimal size ship in LNG carriers - Appios, Prokopis (Τμήμα Εμπορίου, Χρηματοοικονομικών και Ναυτιλίας, Σχολή Διοίκησης και Οικονομίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2013)
The aim of this research is to analyze and interpret the results of the total costs required in shipping LNG through five different routes. Using a mathematical model, which calculates the total cost per day at sea for LNG vessels, we drew conclusions on which size of LNG ship is most suitable for each route in creating economies of scale. In earlier years, the optimal ship was not determined accurately, leading to unprofitable choices and diseconomies of scale. However, due to the globalization of today’s’ markets, shipping companies try to gain competitive advantage by selecting the most suitable vessel in order to create economies of scale. The selection of the optimal ship is determined by the ship’s size, trip duration, capital costs, sailing speed and the demand of LNG at the import country. The empirical results show that the optimal ship for each route is the Q-Max but as the speed decreases, the choices change. By examining the first route, Indonesia-Taiwan, we found that the optimal ship has a capacity of 155.000 m3, sailing with a speed of 16 knots. Moving on to the next route Qatar- Belgium, which is the second longest trip among the analyzed routes, the most suitable ship has a capacity of 216.000 m3 sailing with either 16 or 17 knots. The third route, Qatar-US is the longest trip as it requires between 22 and 24 days for its completion. It is obvious that for this route the preferred ship is the Q-Max sailing with a speed of 19 knots and creating the biggest economies of scale as the variation in costs for this ship is greater in contrast to the other ships sailing with the same speed. The speed is subject to fluctuations based on the weather conditions and on the ship owner’s decision. The next route, Algeria-France, is the shortest trip and thus the optimal size ship is the smallest one with a capacity of 75.000 m3 and speed of 16 knots. Although this ship bears the biggest costs, it can be used in spot markets in order to benefit from the increasing rates from this type of emerging market. The final route, Nigeria-Spain, we chose the ships with capacity of 130.000 m3 and 145.000 m3, both sailing with a speed of 16 knots. The Q-Type vessels were not chosen for this trip, even though they had smaller capital costs than the selected ones. My recommendation to the interested parties is to use this type of mathematical model in order to choose the most costeffective vessel for their voyages. Finally, in order for a more in depth analysis of this study, a selection of further research points is provided.
Keywords: Shipping LNG; Economy